Design of Accounting System by using Micosoft Access on PT. Kisuja Wisata Tours & Travel - Serly Serly; Josephine Ardini Yaputri (ConCEPt - Conference on Community Engagement Project, 2023)
This activity aims to design an accounting record system for business owner. Since the company was established, the company has been doing accounting record manually by using Microsoft Excel. Manual recording is considered as ineffective procedure and it will be hard to find an error if any. Therefore, a systematized accounting record will be more practical so that the company can make decisions easily. First, this activity begins with an interview with the owner to obtain information related such as main activities, internal controls, and others. Then the system was designed by using Microsoft Access 2016 based on company requirements and information. After completing the system, there will be a trial to test the system. Once passed, the system is implemented to the company. The object of this activity is PT. Kisuja Wisata tours & Travel. Through this activity, the business owner can enter transactions through a form and can access financial reports directly.